THU0396 Efficacy and safety of canakinumab in patients with TNF receptor associated periodic syndrome (TRAPS). (23rd January 2014) - Gattorno, M.; Obici, L.; Meini, A.; Tormey, V.; Abrams, K.; Davis, N.; Andrews, C.; Lachmann, H.
Abstract : Background: TNF-receptor associated periodic syndrome (TRAPS) is a rare dominantly inherited periodic fever syndrome involving a genetic mutation of the TNF Super Family Receptor 1A gene. Usually presenting in childhood, it is characterized by recurrent fever attacks associated with rash, musculoskeletal and abdominal pain, conjunctivitis, and periorbital edema and ∼10% develop renal AA amyloidosis. Case reports suggest successful treatment with the IL-1 receptor antagonist anakinra. Canakinumab is a fully human monoclonal selective anti-IL-1β antibody with a half-life of ∼4 wks. Here we report 4-month interim data of canakinumab treatment in patients with active TRAPS. Objectives: To assess the efficacy and safety of canakinumab patients with active TRAPS. Methods: Twenty pts with a median age of 18 years (7 to 78 yrs) and active TRAPS entered a 3-part trial comprising of 4 months of open-label 150mg (or 300mg) sc canakinumab injection every 4 weeks followed by 5 months follow-up (treatment withdrawal), and then 24 months open-label treatment. Pts were evaluated clinically by a 5-point physician's global assessment (PGA) disease activity scale and serologically by CRP and SAA levels. The primary endpoint was complete or almost complete response at Day 15. Complete response was defined as clinical remission (PGA of 0 or 1 [absent or minimal]) and normal CRP and/or SAA. Almost complete response was clinical remission and elevated but ≥70% reduction of baseline CRP and/or SAA. Those who without response by Day 8 were eligible to receive another 150mg sc injection that day and remain at the 300mg dose thereafter. Results: On Day 8, 16 (80%) achieved complete/almost complete response and 18 (90%) achieved clinical remission.The 2 pts without clinical remission were dose up-titrated to 300mg. The primary endpoint was met. At Day 15, 19/20 (95%) achieved complete/almost complete response, including all 4 who did not achieve it at Day 8. Clinical remission was maintained for all from Day 15 onwards in the 4-month treatment period except for 1 patient with a relapse at Day 85 that responded to the scheduled canakinumab dose. Median time to clinical remission was 4 days (95% CI:3, 8). Median baseline CRP (125 mg/L) and SAA (207 mg/mL) normalized to 4mg/L from Day 15 onwards. 95% of patients reported at least 1 adverse event (AE). Infection, mostly upper respiratory tract infections (URI), was the most common (n=13, 65%) category of AE reported. One serious AE, a URI, was reported. All patients continued into the 5 months follow-up and entered the 24-month final open-label treatment period. Conclusions: In this on-going study, canakinumab produced a rapid and highly effective clinical and serological benefit which was maintained with monthly dosing in patients with TRAPS. Canakinumab demonstrated an acceptable safety and tolerability profile in this small study. Data confirm that IL-1β plays a pivotal role in TRAPS and further study is needed to better define canakinumab treatment. Disclosure of Interest: M. Gattorno Grant/Research support from: Novartis, Consultant for: Novartis, Speakers Bureau: Novartis, L. Obici Consultant for: Novartis, A. Meini Consultant for: Novartis, V. Tormey: None Declared, K. Abrams Shareholder of: Novartis, Employee of: Novartis, N. Davis Employee of: Novartis, C. Andrews Shareholder of: Novartis, Employee of: Novartis, H. Lachmann Consultant for: Novartis